2012
DOI: 10.1093/cid/cis1011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tribendimidine Against Clonorchis sinensis

Abstract: Tribendimidine has an efficacy comparable to praziquantel in the treatment of C. sinensis infection and resulted in fewer adverse events compared to praziquantel. Larger clinical trials are warranted among C. sinensis-infected patients to determine the potential of tribendimidine against clonorchiasis and other helminthiases. Clinical Trials Registration.Controlled-Trials.com, ISRCTN80829842.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…A new drug, tribendimidine, appears as effective as praziquantel for clonorchiasis with fewer side-effects (113) . A recent phase two clinical trial demonstrated cure rates up to 91·5% in adults, and up to 98·5% in children in O. viverrini infections treated with 400mg and 100mg of tribendimidine, respectively (114) .…”
Section: For Clonorchis Sinensis Opisthorchis Viverrini and Opisthormentioning
confidence: 99%
“…A new drug, tribendimidine, appears as effective as praziquantel for clonorchiasis with fewer side-effects (113) . A recent phase two clinical trial demonstrated cure rates up to 91·5% in adults, and up to 98·5% in children in O. viverrini infections treated with 400mg and 100mg of tribendimidine, respectively (114) .…”
Section: For Clonorchis Sinensis Opisthorchis Viverrini and Opisthormentioning
confidence: 99%
“…Tribendimidine, artemether and artesuante showed high effectiveness in C. sinensis -infected rats and in vitro and hence might be potential new drug candidates for treating infections [183]. Recently, the Chinese anthelmintic drug tribendimidine was demonstrated to be highly effective against human infections [184]. …”
Section: Resultsmentioning
confidence: 99%
“…Massive drug administration still counts on single drug, praziquantel [27], but no standardized principles of management are yet available. Additionally, tribendimidine, which shows promising efficiency against C. sinensis infection in vivo , in vitro , and in small field test, is expected to be further evaluated [28-30]. …”
Section: Discussionmentioning
confidence: 99%